2020
DOI: 10.1088/1742-6596/1446/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

ICT-based learning media development

Abstract: This research aimed at developing ICT-based learning media for independent learning. The subjects of the research were Mechanical Engineering students of Universitas Sarjanawiyata Tamansiswa. By adopting Borg & Gall’s research and development model, this research was done in four stages, namely: (1) identification stage; (2) design and development stage; (3) production stage; and (4) evaluation stage. Questionnaires were the instrument used for data collection techniques, and the descriptive quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This is because the learning media products developed can be accessed anywhere and at any time. In accordance with Setuju et al (2020) that the rapid development of science and technology in the world of education has caused many developments to occur, such as producing learning media in the form of websites, so that students can access teaching materials anywhere and anytime. Furthermore, Roro et al (2021) say that the presence of e-learning in the world of education is not a substitute for face-to-face learning in the classroom but as a complement.…”
Section: Figure 7 Home Page Using Lontara Bugis Scriptmentioning
confidence: 99%
“…This is because the learning media products developed can be accessed anywhere and at any time. In accordance with Setuju et al (2020) that the rapid development of science and technology in the world of education has caused many developments to occur, such as producing learning media in the form of websites, so that students can access teaching materials anywhere and anytime. Furthermore, Roro et al (2021) say that the presence of e-learning in the world of education is not a substitute for face-to-face learning in the classroom but as a complement.…”
Section: Figure 7 Home Page Using Lontara Bugis Scriptmentioning
confidence: 99%
“…Learning media is able to describe the presentation information and messages, thus facilitating and developing learning processes and outcomes. Learning media can also direct and increase student concentration which can generate learning motivation (Setuju et al, 2020). In the learning process, the media is able to grow the learning process of students in the learning process, which will ultimately improve the learning outcomes achieved by Lembaho et al (2022) found Learning is basically a process of communication.…”
Section: Exploring Teachers' Perception About Rosetta Stone As a Read...mentioning
confidence: 99%
“…Today, Science and Technology is developing rapidly and development is aimed at the world of education. Learning by utilizing technological developments aims to create a dynamic and interactive learning environment inside and outside the classroom (Gendall, 2008;Setuju, Ratnawati, Wijayanti, Widodo, & Setiadi, 2020). Therefore, the use of instructional media that includes innovations and interactive features must be considered and adjusted to the current development so that the learning process can be carried out optimally.…”
Section: Interactive Multimediamentioning
confidence: 99%